Use of a quality improvement strategy to increase drug and alcohol consultation and care opportunities for mental health inpatients in rural and remote New South Wales. (20th June 2021) - Kealy‐Bateman, Warren; Christian, Namrata; Wetton, Rebecca; Bruce, Billy‐Jo; Rowe, Deborah; McIntyre, Sharon
Abstract: Problem: Mental health inpatients have high rates of co‐morbid substance use disorders which may exceed 50% in addition to the presenting complaint(s). Treating teams may prioritise, and substance use disorders are often not addressed. Setting: Dubbo inpatient mental health units. Key measures for improvement: Rates of drug and alcohol consult of inpatients. Design: Retrospective audit of all inpatient records for mental health units at Dubbo Hospital (May‐October period 2018 and 2019) following the intervention. Qualitative reflections of clinical staff were also included. Strategies for change: From early 2019, the problem was communicated with staff via education and open discussion. Modelling of the expected numbers of referral was understood as manageable within existing resources. The agenda of the morning meeting then always included an item that asked all team members to identify and refer a person if they needed drug and alcohol care. Effect of change: Consultation by the drug and alcohol clinical nurse consultant increased from 48 of 228 (21%) patients in the 2018 period to 83 of 232 (35.8%) patients in the 2019 period. Lessons learnt: The community and inpatient multidisciplinary team can correctly inform and increase drug and alcohol referral for mental health inpatients.